(untitled) (World Bulletin of Public Health, 2022)
The COVID-19 pandemic was characterized by psychosomatic effects along with socioeconomic impacts. We aimed to study sexual behavioral disorders after the COVID-19 pandemic in patients with alcoholism. The study found that one of the possible factors determining the development of sexual dysfunction is the type of sexual constitution. A number of factors have been found to influence the formation of sexually transmitted diseases in alcoholdependent patients with COVID-19. COVID-19 plays an important role in the formation of pathology in the genital area.